Pelvic pain and indirect findings of endometriosis on pelvic ultrasound: A statistical correlation (Research, Society and Development, 2021)
Objective: To identify the prevalence of women with pelvic pain, how many have findings suggestive of endometriosis on USG, and the most frequent endometriosis findings and stratification of the prevalence of these ultrasound changes by age group.. Methodology: This is a documentary research that assesses the prevalence of how many women with chronic pelvic pain have indirect findings of endometriosis on ultrasound, thus having a quantitative approach, having as place of study a private clinic called Clínica Valle Imagem in the city of Itaporanga - Paraíba, comprising a population of 87 women with pelvic pain. The collection instruments were data from reports and medical records of ultrasound exams of patients with pelvic pain. Results: It was observed that of the 87 women who presented clinical signs of endometriosis/adenomyosis such as chronic pelvic pain, dyspareunia and infertility, 79 presented changes on ultrasound that suggested endometriosis. Conclusion: Although USG is not the best method to diagnose endometriosis, since MRI and laparoscopy are the first choice, USG is a useful method for evaluation of patients with chronic pelvic pain because of its availability, low cost, and because it is innocuous and minimally invasive.